2011
DOI: 10.1016/j.fertnstert.2011.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Racial influence on the polycystic ovary syndrome phenotype: a black and white case-control study

Abstract: Objective To estimate racial disparities in PCOS phenotype between White and Black women with PCOS. Design Case/control study Setting Two academic medical centers Patients 242 women off of confounding medications in otherwise good health Interventions Phenotyping during the follicular phase or anovulation after overnight fast in women. Main outcome measures Biometric, serum hormones, glycemic and metabolic parameters, and body composition by DEXA. Results We studied 77 White and 43 Black women with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 20 publications
3
27
0
1
Order By: Relevance
“…In addition to sample size, most of the studies that have been performed around the world have argued that there are also racial differences in the distribution patterns of PCOS phenotypes [1417]. However, this was not supported by a case-control study that was performed by Ladson et al [18], which revealed that differences between black and white PCOS women were minimal.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to sample size, most of the studies that have been performed around the world have argued that there are also racial differences in the distribution patterns of PCOS phenotypes [1417]. However, this was not supported by a case-control study that was performed by Ladson et al [18], which revealed that differences between black and white PCOS women were minimal.…”
Section: Discussionmentioning
confidence: 99%
“…The wide range of 4–18% in the reported prevalence of PCOS is likely to reflect the different criteria used in the diagnosis of the condition. The prevalence of PCOS across different ethnic groups is largely similar, but ethnicity does seem to affect the clinical and metabolic presentation of these women . Higher rates of type 2 diabetes (T2DM) and cardiovascular events in women with PCOS have been reported previously, and South Asian (SA) ethnicity was associated with diabetes and not with cardiovascular events .…”
Section: Introductionmentioning
confidence: 89%
“…Due 64 to the eventual weight gain and cancer risks of thiazolidinediones, 65 prescription of these drugs has been limited only to diabetic 66 patients [4]. In women with PCOS, treatment with metformin 67 ameliorated the cardio-metabolic profile by improving insulin 68 sensitivity, lowering blood glucose and androgen levels, possibly 69 acting through body weight changes [5][6][7][8]. Metformin is more 70 active than oral contraceptives in reducing fasting insulin not 71…”
mentioning
confidence: 99%